Crucifying Desires—Desires Crucified. On the Meaning of Two Crucifixion Metaphors (Seneca De vita beata 19.3; Gal 5:24) - du Toit, David (At the Borders of the New Testament (Studies in Honor of Johan C. Thom), 2022)
In his chapter, “Crucifying Desires—Desires Crucified”, David du Toit explores the meaning of the crucifixion metaphors in Gal 5:24 and Seneca’s De vita beata 19.3. Du Toit demonstrates that the interpretation of the two metaphors depends on the argumentative and metaphorical context provided by the literary context. He also shows that knowledge of the semantic encyclopedia and a specific set of semantic associations is a prerequisite for an adequate understanding of the metaphors. The discussion of the texts makes clear that De vita 19.3 can help to make better sense of Paul’s crucifixion metaphor in the Galatians passage.<br